Evaluating the function of cross‐linked rice starch as a fat replacer in low fat cream. (15th May 2018) - Bagheri, Foroud; Radi, Mohsen; Amiri, Sedigheh
Abstract : The aim of this study was to investigate the application of high and low amylose cross‐linked rice starches as fat replacers in low fat cream at 5, 10, and 15% (w/w). According to scanning electron microscopy, no morphological changes were observed on the starch granules due to cross‐linking, while the mean diameter of the granules and their swelling power decreased. The firmness and freeze–thaw stability of the creams significantly increased with starch concentration. Creaminess was not affected at 5% substitution. The results indicated that 5% fat replacement with either high or low amylose, native or cross‐linked rice starches would produce creams with good sensory and physico‐chemical properties.